Financial Performance and Islamic Stock Return: a Price to Book Value Role - Fachruddin, Mukhammad Hafidh; Aisyah, Esy Nur (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return on Assets (RoA), Return on Equity (RoE), and Earnings per Share (EpS) on stock returns in companies listed in the Jakarta Islamic Index (JII) for the 2020–2024 period, with Price to Book Value (PBV) as a mediating variable. A quantitative approach was used with secondary data in the form of quarterly financial reports from 12 companies that met the purposive sampling criteria. Data analysis was conducted using panel data regression with a Random Effects Model (REM) and the Sobel test to test the mediating effect of PBV. The results showed that RoA, RoE, and EpS significantly influenced PBV, while DER did not. The stock return model, RoA, and PBV proved to have a significant effect, while DeR, RoE, and EPS did not have a direct effect. The mediation test showed that PBV was unable to mediate the effect of DER, RoA, RoE, or EpS on stock returns. This finding indicates that profitability and market valuation factors have a more dominant role than capital structure in influencing sharia stock returns in JII.